Flood adaptation and mitigation in the Awash Basin: responding to new climate patterns - Taye, Meron Teferi; Haile, Alemseged Tamiru; Dessalegn, Mengistu; Nigussie, Likimyelesh; Bekele, Tilaye Worku; Nicol, Alan; Dyer, E. (University of Oxford, 2024)
The Awash Basin in Ethiopia experiences frequent flooding, sometimes with devastating consequences. Climate change is now creating new flood regimes in different parts of the basin and reshaping the interaction of flooding with rapidly changing communities. This is causing heightened risk, particularly for the most vulnerable communities across the basin, and requires new forms of management and response.